تطبيق منهج التصوير الفني لسيد قطب في فهم سورة يوسف واستيعابها - Siti Salma Wahiduddin; Nasr El Din Ibrahim Ahmad Hussein; Wan Azura Wan Ahmad (Usim Press, 2024)
Ulum Islamiyyah: Malaysian Journal of Islamic Sciences Volume 35 No.3 Page (25-38)